Motor Sequence Learning across Multiple Sessions Is Not Facilitated by Targeting Consolidation with Posttraining tDCS in Patients with Progressive Multiple Sclerosis - Harald Seelmann-Eggebert; Muriel Stoppe; Florian Then Bergh; Joseph Classen; Jost-Julian Rumpf (Neural Plasticity)
Compared to relapsing-remitting multiple sclerosis (MS), progressive MS is characterized by a lack of spontaneous recovery and a poor response to pharmaceutical immunomodulatory treatment. These patients may, therefore, particularly benefit from interventions that augment training-induced plasticity of the central nervous system. In this cross-sectional double-blind cross-over pilot study, effects of transcranial direct current stimulation (tDCS) on motor sequence learning were examined across four sessions on days 1, 3, 5, and 8 in 16 patients with progressive MS. Active or sham anodal tDCS of the primary motor cortex was applied immediately after each training session. Participants took part in two experiments separated by at least four weeks, which differed with respect to the type of posttraining tDCS (active or sham). While task performance across blocks of training and across sessions improved significantly in both the active and sham tDCS experiment, neither online nor offline motor learning was modulated by the type of tDCS. Accordingly, the primary endpoint (task performance on day 8) did not differ between stimulation conditions. In sum, patients with progressive MS are able to improve performance in an ecologically valid motor sequence learning task through training. However, even multisession posttraining tDCS fails to promote motor learning in progressive MS.